(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the creation and promotion of regional innovation clusters based on international experience and empirical evidence from successful cluster initiatives during 2018-2024, examining policy frameworks, institutional mechanisms, and economic outcomes that drive innovation-based regional development and competitive advantage.